Pengaruh Perlakuan Autoclaving-Cooling Terhadap Karakteristik Tepung Kecambah Milet (Panicum miliaceum L.) Terfermentasi - Aurell Divas; I Desak Putu Kartika Pratiwi; Ni Nyoman Puspawati (Study Program of Food Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Abstract Millet (Panicum miliaceum L.) is a cereal belonging to the Poaceae family whose utilization as a food ingredient remains limited. Processing millet grains into flour and applying physical modification techniques are required to improve its chemical and functional properties. This study aimed to determine the differences in characteristics of fermented millet sprouts flour before and after autoclaving–cooling treatment and to evaluate the effect of this modification. The experiment employed a paired t-test design with two treatments: fermented millet sprouts flour without autoclaving–cooling and with autoclaving–cooling at 121°C for 15 minutes, each performed in five replications. Parameters observed included yield, moisture content, starch content, amylose content, amylopectin content, water absorption capacity, oil absorption capacity, and swelling power. The results showed that autoclaving–cooling treatment significantly affected (p<0.05) all observed parameters. The treatment increased starch content, amylose content, water absorption capacity, oil absorption capacity, and swelling power, while decreasing amylopectin content and flour yield. In conclusion, autoclaving–cooling modification effectively improved the chemical and functional characteristics of fermented millet sprouts flour, indicating its potential application in various flour-based food products. Keywords: millet flour, sprouts, fermentation, autoclaving–cooling Abstrak Milet (Panicum miliaceum L.) merupakan serealia dari famili Poaceae yang pemanfaatannya sebagai bahan pangan masih terbatas. Pengolahan biji milet menjadi tepung serta penerapan modifikasi fisik diperlukan untuk meningkatkan karakteristik kimia dan fungsionalnya. Penelitian ini bertujuan untuk mengetahui perbedaan karakteristik tepung kecambah milet terfermentasi sebelum dan sesudah perlakuan autoclaving–cooling serta mengevaluasi pengaruh perlakuan tersebut. Penelitian menggunakan uji t berpasangan dengan dua perlakuan, yaitu tepung kecambah milet terfermentasi tanpa autoclaving–cooling dan dengan autoclaving–cooling pada suhu 121°C selama 15 menit, masing-masing diulang lima kali. Parameter yang diamati meliputi rendemen, kadar air, kadar pati, kadar amilosa, kadar amilopektin, kapasitas penyerapan air, kapasitas penyerapan minyak, dan swelling power. Hasil penelitian menunjukkan bahwa perlakuan autoclaving–cooling berpengaruh nyata (p<0,05) terhadap seluruh parameter yang diamati. Perlakuan ini meningkatkan kadar pati, kadar amilosa, kapasitas penyerapan air, kapasitas penyerapan minyak, dan swelling power, serta menurunkan kadar amilopektin dan rendemen tepung. Dengan demikian, modifikasi autoclaving–cooling dapat memperbaiki karakteristik kimia dan fungsional tepung kecambah milet terfermentasi sehingga berpotensi diaplikasikan pada berbagai produk pangan berbasis tepung. Kata kunci: tepung milet, kecambah, fermentasi, autoclaving–cooling